Mineral content of the forearms of babies born to Asian and white mothers. Issue 6373 (16th April 1983) - Congdon, P; Horsman, A; Kirby, P A; Dibble, J; Bashir, T
Abstract : Vitamin D deficiency is common in pregnant Asian women. The effect of maternal vitamin D deficiency on fetal skeletal mineralisation was assessed by measuring the bone mineral content of babies born to 45 Asian women, 19 Asian women who had received 1000 units of vitamin D during the last trimester, and 12 white women. The mean cord blood concentrations of 25-hydroxy vitamin D in the three groups were 5.9 +/- SE 0.9 nmol/l (2.4 +/- SE 0.4 ng/ml), 15.2 +/- 3.2 nmol/l (6.1 +/- 1.3 ng/ml), and 33.4 +/- 3.6 nmol/l (13.4 ng/ml), respectively. Despite this wide variation in values there was no significant difference in the bone mineral content (as assessed by photon absorptiometry) of the forearms of babies born to these women. This suggests that mineralization of the fetal skeleton is not impaired in maternal vitamin D deficiency. Craniotabes (skull softening) was present in seven of the 64 Asian babies. The bone mineral content in these babies was not significantly different from that of babies without this sign, and craniotabes should not therefore be taken as an indication of a generalized impairment in skeletal mineralization.